2022
DOI: 10.1002/agj2.21001
|View full text |Cite
|
Sign up to set email alerts
|

Transitional organic forage systems in the southeastern U.S.: Production and nutritive value

Abstract: Limited work has been done to develop organic forage programs in humid subtropical regions despite growing demand for high‐value forage and organic products. Alternative crops were compared for optimizing forage production and nutritive value under organic conditions in the southeastern United States. The study was conducted at the Middle Tennessee AgResearch and Education Center, in Spring Hill, Tennessee. Forage treatments consisted of (a) monoculture tall fescue [Schedonorus arundinaceus (Schreb.) Dumort.],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A more detailed description of the experimental site and study design can be found in Kubesch et al. (2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more detailed description of the experimental site and study design can be found in Kubesch et al. (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Initial soil nutrient levels were similar across the experiment site and were determined by Mehlich 1 extract to be pH = 6.3, P = 63 ppm, K = 160 ppm, Ca = 1009 ppm, and Mg = 161 ppm. A detailed description of the experimental site and study design can be found in Kubesch et al (2022).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Red clover ( Trifolium pratense L.) is a globally important perennial legume widely utilized in temperate regions as forage for ruminants. It has high feed value due to its high digestibility and crude protein concentration. , Dairy diets containing legumes, such as red clover, increase milk yield and quality , and have been associated with reductions in methane yield (g/kg of dry matter intake) and methane intensity (g/kg of energy-corrected milk in dairy cattle) . Additionally, red clover fixes atmospheric nitrogen (N), thereby reducing the need for synthetic N fertilizers and their negative impacts on the environment including formation of the greenhouse gas N 2 O. …”
Section: Introductionmentioning
confidence: 99%